In situ compressibility of carbonated hydroxyapatite in tooth dentine measured under hydrostatic pressure by high energy X-ray diffraction. (October 2015) - Forien, Jean-Baptiste; Fleck, Claudia; Krywka, Christina; Zolotoyabko, Emil; Zaslansky, Paul
Abstract: Tooth dentine and other bone-like materials contain carbonated hydroxyapatite nanoparticles within a network of collagen fibrils. It is widely assumed that the elastic properties of biogenic hydroxyapatites are identical to those of geological apatite. By applying hydrostatic pressure and by in situ measurements of the a - and c - lattice parameters using high energy X-ray diffraction, we characterize the anisotropic deformability of the mineral in the crowns and roots of teeth. The collected data allowed us to calculate the bulk modulus and to derive precise estimates of Young׳s moduli and Poisson׳s ratios of the biogenic mineral particles. The results show that the dentine apatite particles are about 20% less stiff than geological and synthetic apatites and that the mineral has an average bulk modulus K =82.7 GPa. A 5% anisotropy is observed in the derived values of Young׳s moduli, with E 11 ≈91 GPa and E 33 ≈96 GPa, indicating that the nanoparticles are only slightly stiffer along their long axis. Poisson׳s ratio spans ν≈0.30–0.35, as expected. Our findings suggest that the carbonated nanoparticles of biogenic apatite are significantly softer than previously thought and that their elastic properties can be considered to be nearly isotropic.